Answer:
a = 3/28
Explanation:
To start solving for a variable, you need to isolate it.
-4/3b = 4a
-4/3 divided by 4 equals -4/12 or -1/3
a = -1/3b
To completely solve for a we need to plug it back in and solve for b.
b = (4(-1/3b)) - 3/4
b = -4/3b - 3/4
7/3b = -3/4
b = -9/28
Finally, we can plug b back in to the previous equation we got for a to solve for a.
a = -1/3(-9/28)
a = 3/28
Furthermore, we can check if this is correct by plugging in 3/28 for a into the original problem and see if we get what we got for b (-9/28)